Association between Early Body Weight Loss and Development of Hyperbilirubinemia in Term Neonates at 72 Hours - Dr Deepak Sankhwar; Dr. Praveen Anand; Dr Koushik Ray (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Neonatal hyperbilirubinemia affects approximately 60% of term and 80% of preterm newborns according to AIIMS NICU protocols, representing one of the most common neonatal conditions requiring clinical intervention. Early body weight loss patterns may serve as predictive indicators for subsequent jaundice development, particularly in resource-limited settings where simple monitoring tools are essential for timely intervention. Methods: A prospective observational cohort study was conducted at the Autonomous State Medical College, Fatehpur, Uttar Pradesh, from January to December 2024. Term neonates (≥37 weeks gestation, birth weight >2500g) were enrolled and monitored for body weight loss patterns during the first 72 hours. Total serum bilirubin levels were measured at 72 hours, with hyperbilirubinemia defined as ≥12 mg/dL for term infants, following AIIMS NICU protocol guidelines. Receiver operating characteristic curve analysis determined optimal weight loss thresholds, and multivariate logistic regression identified independent risk factors. Results: Among 380 enrolled neonates, 228 (60.0%) developed hyperbilirubinemia at 72 hours, consistent with AIIMS protocol observations. Hyperbilirubinemic neonates experienced significantly higher weight loss at all-time points (day 3: 9.2±2.8% vs 5.8±2.1%, p < 0.001). The optimal predictive threshold was 7.8% weight loss at 72 hours (sensitivity 78.5%, specificity 81.2%, AUC=0.863). Independent risk factors included maximum weight loss >7.5% (OR = 4.12, 95% CI: 2.48-6.85), decreased gestational age (OR = 1.75 per week), primiparity (OR = 1.89), and reduced breastfeeding frequency (OR = 2.28). Conclusion: Early neonatal body weight loss patterns, particularly exceeding 7.8% at 72 hours, strongly predict hyperbilirubinemia development in 60% of term neonates. This simple anthropometric assessment provides a practical screening tool for identifying high-risk neonates, enabling timely interventions and optimized clinical management consistent with AIIMS NICU protocols.